PERILAKU HUBUNGAN EKSTERIOR BALOK-KOLOM BETON PRACETAK SISTEM KOLOM BERBENTUK - T - Fitrah Nar, Oscar
The experimental research is conducted to study the behavior of external beam column joint with used T shape column under quasi-static cyclic reverse loading at the top of column. The object of the research are two specimens of beam column joint with the same compressive strength and dimension. The difference of two specimens are reinforced of beam and column, and the axial load is given. The specimen consist of precast beam and column, cast in situ joint, where the shape of precast beam is half - I and the shape of precast column is T. The result of hysteresis load-displacement curve, ductility, energy dissipation strength and stiffness degradation were analyzed from experimental work. Crack pattern and propagation were also observed and studied. Crack pattern show that the collapse of the unit is due to flexural action under ductile manner. It means that the strong column - weak beam concept for beam column joint design under seismic load is satisfactory. This is shown by the experimental study that the column and joint were behaving elastically while plastic hinge developed at the beam on the column face